(untitled) (International Journal of Engineering and Computer Science, 2017)
The weather temperature computation procedure has been discussed. This paper presents an application of Discrete Fourier Transformation (DFT) technique for weather temperature computation. This temperature computation is based on the previous daily maximum temperature. The experimental result of the temperature computed can found to be in good agreement with the data obtained from Bangladesh Meteorological Department.